The relationship between internal control and credit risk: The case of commercial banks in Vietnam - Nguyen Kim Quoc Trung (Cogent Business & Management, 2021)
This study examines whether the agency problem regarding credit risk is a useful corporate governance mechanism for controlling credit risk. For this purpose, we estimate the impact of internal control and agency problems on credit risk in commercial banks in Vietnam from 2009 to 2018. First, in line with corporate governance theory, we find that the agency problem is a statistically significant variable in the model. This result expands the existing literature. Second, we show that internal control is a mechanism to resolve the conflict of interest between the principal and agent. The author especially emphasizes the unchanged correlation of each independent variable to the dependent variable during the merger and restructuring of Vietnamese commercial banks in 2015.
Keywords: M1; G32; E51; E58; G21; 650; credit risk; internal control; agency problem; leverage ratio; Bank